2015
DOI: 10.1002/em.21941
|View full text |Cite
|
Sign up to set email alerts
|

Development of a toxicogenomics signature for genotoxicity using a dose‐optimization and informatics strategy in human cells

Abstract: The development of in vitro molecular biomarkers to accurately predict toxicological effects has become a priority to advance testing strategies for human health risk assessment. The application of in vitro transcriptomic biomarkers promises increased throughput as well as a reduction in animal use. However, the existing protocols for predictive transcriptional signatures do not establish appropriate guidelines for dose selection or account for the fact that toxic agents may have pleiotropic effects. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
132
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 88 publications
(134 citation statements)
references
References 42 publications
2
132
0
Order By: Relevance
“…We utilized gene expression data derived in a recent study in which TK6 cells were exposed to 45 chemicals for 4 hr followed by analysis using nCounter (Li et al, ) (The list of chemicals is found in Supplemental File 1). As part of this study, the original training set of 27 treatments (26 chemicals and γ‐rays) used to derive the TGx‐DDI biomarker (Li et al, ) were examined for gene expression effects in TK6 cells using nCounter. The 27 chemicals included 13 true positives and 14 true negatives.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We utilized gene expression data derived in a recent study in which TK6 cells were exposed to 45 chemicals for 4 hr followed by analysis using nCounter (Li et al, ) (The list of chemicals is found in Supplemental File 1). As part of this study, the original training set of 27 treatments (26 chemicals and γ‐rays) used to derive the TGx‐DDI biomarker (Li et al, ) were examined for gene expression effects in TK6 cells using nCounter. The 27 chemicals included 13 true positives and 14 true negatives.…”
Section: Resultsmentioning
confidence: 99%
“…Our method for identification of chemicals that cause DNA damage is outlined in Figure A and required the following: (a) a list of TGx‐DDI biomarker genes with associated fold‐change values; (b) gene expression profiles of statistically filtered genes (also called biosets); and (c) a method to compare the biomarker to each bioset. These components are described below. The TGx‐DDI biomarker is a list of differentially expressed genes (DEGs) that were consistently increased or decreased after exposure to 13 DDI agents but not non‐DDI agents in TK6 cells (Li et al, ). The biomarker includes fold‐change values associated with each gene, derived from the average differences in expression across the 13 DDI agents. Statistically filtered gene lists were analyzed in a commercially available gene expression database called BaseSpace Correlation Engine (BSCE) ( https://www.illumina.com/products/by‐type/informatics‐products/basespace‐correlation‐engine.html; formally NextBio). The TGx‐DDI gene biomarker was uploaded to the BSCE database and compared to the biosets used in this analysis to assess correlation using the Running Fisher algorithm (Kupershmidt et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations